ANALISIS POTENSI PENERIMAAN PENDAPATAN ASLI DAERAH DARI RETRIBUSI KIER TAKSI GELAP DI KABUPATEN MIMIKA - Urbanus Fangohoi; Stepanus Sandy (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2020)
The purpose of this research is to determine the potential revenue of the Taxicab Kier Test in Mimika Regency and to determine the contribution of the TaxiCab Kier Test to PAD Mimika Regency. The data collection techniques used in this study were observation, interviews, documentation and literature study. The analysis used in this research is to conduct an analysis of the potential revenue of local revenue from the Kier Taxicab levies. The results of this study indicate that the testing of motorized vehicles against taxiscabs operating in the City of Timika has the potential to increase local revenue or increase fees from motorized vehicle testing